2023
DOI: 10.1177/1420326x221148729
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the thermal performance of radiant floor heating system with the influence of solar radiation on the local floor surface

Abstract: In some buildings with radiant floor systems for heating, solar radiation can irradiate the local floor surface, causing overheating and affecting the heating performance of the radiant floor. In this paper, an experiment was carried out to study the thermal performance of radiant floor partially irradiated by solar radiation. Results show that the solar radiation can promote the heat transfer from the irradiated floor to the room and reduce the heat transfer from the hot water to the floor. Compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The radiant heat transfer between a certain human body and radiant panels is largely affected by other indoor objects [21] or complex shapes of rooms [28]. In addition, some researchers have suggested that solar radiation through windows may affect the results related to the MRT [45,46] and thermal comfort [47,48], which was not mentioned in this study. In further research and investigation, situations in which objects interpose, areas have complex shapes, and the effect of solar radiance should be addressed to enlarge the application of the HNU Angle Factor Model.…”
Section: Limitationsmentioning
confidence: 79%
“…The radiant heat transfer between a certain human body and radiant panels is largely affected by other indoor objects [21] or complex shapes of rooms [28]. In addition, some researchers have suggested that solar radiation through windows may affect the results related to the MRT [45,46] and thermal comfort [47,48], which was not mentioned in this study. In further research and investigation, situations in which objects interpose, areas have complex shapes, and the effect of solar radiance should be addressed to enlarge the application of the HNU Angle Factor Model.…”
Section: Limitationsmentioning
confidence: 79%
“…In recent times, several innovative papers on radiant heating have also been published. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Wu et al 1 investigated the thermal responses and the thermal environmental parameters of various indoor and outdoor spaces to compare the thermal comfort of these spaces. In the study by Zhang et al 2 a two-dimensional numerical model of the floor heating system combined with the phase-change materials has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…A two-dimensional heat transfer model of the radiant cooling panel with multiple air layers was established to remove condensation problems with the heating cooling system. Zheng et al 17,18 studied the thermal performance of a partially irradiated radiant floor by solar radiation. Results showed that solar radiation can promote the heat transfer from the irradiated floor to the room and reduce the heat transfer from the hot water to the floor.…”
Section: Introductionmentioning
confidence: 99%